2015
DOI: 10.1210/jc.2015-1261
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia Is Associated With Increased Osteoporosis and Bone Fractures in a Large US Health System Population

Abstract: These analyses support the hypothesis that hyponatremia is a risk factor for osteoporosis and fracture. Additional studies are required to evaluate whether correction of hyponatremia will improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 31 publications
3
68
1
2
Order By: Relevance
“…These last two drug classes are associated with altered metabolism and absorption of calcium, phosphate, and vitamin D, and trabecular bone loss at the spine and femoral neck (6, 13-17). In addition, hyponatremia, an emerging contributor to osteoporosis, has been reported after allo-HSCT (18-20). …”
Section: Introductionmentioning
confidence: 99%
“…These last two drug classes are associated with altered metabolism and absorption of calcium, phosphate, and vitamin D, and trabecular bone loss at the spine and femoral neck (6, 13-17). In addition, hyponatremia, an emerging contributor to osteoporosis, has been reported after allo-HSCT (18-20). …”
Section: Introductionmentioning
confidence: 99%
“…As has been described in other studies, PH was associated with older age, systemic hypertension, diabetes, and a history of heart failure (HF). 5,7 Multivariable analysis found that older age, lower hemoglobin, lower left ventricular ejection fraction, and the presence of left ventricular hypertrophy were independently associated with PH. The presence of PH was associated with a 38% increased risk of overall mortality and a 23% increased risk of cardiovascular events (HF, myocardial infarction, cerebrovascular accident, and peripheral vascular disease).…”
Section: Disclosuresmentioning
confidence: 99%
“…Furthermore, in population-based studies, chronic hyponatremia associates with bone fracture risk [6][7][8] ; however, whether this is a consequence of a neurologic phenotype predisposing to falls 9 or of a bone phenotype predisposing to fracture 10 (or perhaps a combination of both) remains unclear.…”
mentioning
confidence: 99%
“…1 It has been detected as the most frequent electrolyte disorder in clinical medicine. 2,3 Mild hyponatraemia is seldom associated with any specific features and symptoms usually relate to the underlying cause of the hyponatraemia. Severity of symptoms depends on rate of fall of plasma sodium concentration as well as absolute value.…”
Section: Introductionmentioning
confidence: 99%